FATORES DOS PRIMEIROS 1000 DIAS DE VIDA ASSOCIADOS À SINTOMAS ASMA NA INFÂNCIA NA COORTE BRISA EM SÃO LUÍS E RIBEIRÃO PRETO, BRASIL. - NASCIMENTO, Joelma Ximenes Prado Teixeira (2018)
Asthma is a complex syndrome, of difficult diagnosis in children. The mechanisms involved in the etiopathogeny of the disease have not been completely elucidated. Environmental exposures during the first 1000 days of life (270 days of gestation plus the 365 days of the first year of life and 365 days of the second of life) appear to have a strong influence on epigenetic regulation, increasing predisposition to childhood asthma. The association between early exposures of the prenatal period, birth and the first years of life with asthma symptoms in children involves multicausality and temporality relationships between these variables that can be better studied by structural equation modeling (SEM). Chapter I of this thesis was the original article: The First 1000 Days of Life Factors Associated with “Childhood Asthma Symptoms”: Brisa Cohort, São Luís, Brazil, which aimed to analyze the associations between the environmental factors up to the first 1000 days of life and “Childhood Asthma Symptoms”. It is a prospective study involving three moments of the BRISA cohort in Sao Luis (n = 1140), where the outcome was the latent variable “Childhood Asthma Symptoms”, formed by four indicators with convergent loads: medical diagnosis of asthma, number of wheezing episodes, emergency care visit due to wheezing and medical diagnosis of rhinitis. A theoretical model that included prenatal factors, birth factors and of the second year of life, were analyzed in association with “Childhood Asthma Symptoms” using SEM. It was observed that the higher the pre-gestational BMI, high soft drink consumption in gestation, cesarean section without labor, chill in the first three months of life, carpeted floor and child´s exposure to tobacco were associated with higher values of “Childhood Asthma Symptoms”. In contrast, high birth weight, the age of the child and children exclusively breastfed for six months were associated with lower values of “Childhood Asthma Symptoms”. Chapter II of this thesis was the original article: Environmental factors linked microbiota hypothesis and “Childhood Asthma Symptoms”: BRISA cohort, Ribeirão Preto, Brazil, which aimed to analyze environmental factors linked to the microbiota hypothesis and “Childhood Asthma Symptoms”. It is a prospective study involving population-based sample of the BRISA birth cohort in Ribeirão Preto (n = 3694). Birth and second year life factors linked to the microbiota hypothesis were analyzed on a theoretical model having as outcome the latent variable “Childhood Asthma Symptoms” was formed by three indicators (medical diagnosis of asthma, number of wheezing episodes and emergency care visit due to wheezing) using SEM. It was observed that children with higher BMI values, belonging to the black race, with diarrhea and older presented higher values for “Childhood Asthma Symptoms”; while better economic situation, female gender and longer breastfeeding presented lower values for “Childhood Asthma Symptoms”. In the present thesis, the analyzes of the variable “Childhood Asthma Symptoms” as a continuous latent formed by clinical indicators of convergent loads reduced the error of measurement of this outcome difficult to diagnose in children. Our findings suggest that environmental exposures during the first 1000 days of life, such as: maternal and child overweight, consumption of soft drinks in gestation, cesarean delivery, would be involved in the early programming of asthma children, while breastfeeding would protect from this condition.